Efek Ekstrak dan Fraksi Herbal Peperomia pellucida (L.) Kunth., Terhadap Beberapa Bakteri Patogen Kulit - Nurbaity Situmorang (Universitas Medan Area, 2018)
The study of extract and fraction of Peperomia pellucida (L.) Kunth., herbal’s against several dermal pathogenic bacteria have been carried out in Research Laboratory of Pharmacy Department and Microbiology and Micology Laboratory Biology Department Faculty Mathematic and Natural Sciences Andalas University and Regional Medical Laboratory Center in Gunung Pangilun Padang from July until October 2007. Three kinds of dermal pathogenic bacteria were used : Staphylococcus aureus, Staphylococcus epidermidis and Proteus vulgaris. Antimicrobial activity was determined base on their MIC (Minimal Inhibitory Concentration) and MBC (Minimal Bactericidal Concentration) through dilution method that used “Microtiterplate 96-well”. The Result showed that the best activity of herbal extract was against Proteus vulgaris (MIC 7,81 ppm and MBC 125 ppm). The most active fraction was showed in n-hexane against Proteus vulgaris (MIC 0,63 ppm and MBC 250 ppm), the etil acetat fraction (MIC 2,50 ppm and MBC 500 ppm), while the activity of n-butanol and aquaeous fraction (MIC 5 ppm and MBC 500 ppm, respectively).